Die woord van God as lewende, kragtige en tweesnydende sward - 'n studie van hebreërs 4:12-13 binne die konteks van die hele Hebreërs - Coetzee, J. C. (Koers, 1988)
Within the wider scope of interdisciplinary studies on The Power of the Word of God this article gives a New Testament perspective on the theme through an exegetical study of Hebrews 4:12-13 within its broader context. Whilst this pericope is often used as a prooftext (locum probantium) for the divine authority of Scriptures this study starts on the as sumption that this is not the primary focus of the text. It is as sumed that the text is primarily concerned with the effective power of God's Word in the lives of men, especially In the lives of members of God's people. Four hypotheses are stated at the beginning and are exegetically tested in the article: (i) In the whole Bible Hebrews 4:12-13 is one of the clearest and most compact expressions of the dynamic power of the Word of God. (ii) Hebrews 4:12-13 is indeed a cornerstone in the message of this sermon to "the Hebrews". (HI) Although various Biblical passages seemingly have strong parallels on the matter of the power of the Word Hebrews 4:12-13 proves to have a singular emphasis, namely of the living, powerful and the decisively penetrating power of JUDGE of the deepest heart of man. (iv) Hebrews 4:12-13 within its context gives an important portrait of the most intimate relation between the Word of God and the God of the Word.